2015
DOI: 10.1785/0120140332
|View full text |Cite
|
Sign up to set email alerts
|

Regionally Adjustable Generic Ground‐Motion Prediction Equation Based on Equivalent Point‐Source Simulations: Application to Central and Eastern North America

Abstract: We develop a generic ground-motion prediction equation (GMPE) that can be adjusted for use in any region by modifying a few key model parameters. The basis of the GMPE is an equivalent point-source simulation model whose parameters have been calibrated to empirical data in California, in such a way as to determine the decoupled effects of basic source and attenuation parameters on ground-motion amplitudes. We formulate the generic GMPE as a function of magnitude, distance, stress parameter, geometrical spreadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(81 citation statements)
references
References 41 publications
3
73
0
1
Order By: Relevance
“…A strong geometrical spreading at short and intermediate distances is observed in other worldwide regions, such as Western North America (Atkinson 2004;Babaie Mahani & Atkinson 2012) and Central and Eastern America (Yenier & Atkinson 2015). Numerical simulations in a typical layered medium also indicate that the distance decay in the epicentral area can be described by geometrical spreading with exponent greater than 1 (Frankel 1991;Chapman & Godbee 2012).…”
Section: R E S U Lt S Attenuation Functionsmentioning
confidence: 77%
See 1 more Smart Citation
“…A strong geometrical spreading at short and intermediate distances is observed in other worldwide regions, such as Western North America (Atkinson 2004;Babaie Mahani & Atkinson 2012) and Central and Eastern America (Yenier & Atkinson 2015). Numerical simulations in a typical layered medium also indicate that the distance decay in the epicentral area can be described by geometrical spreading with exponent greater than 1 (Frankel 1991;Chapman & Godbee 2012).…”
Section: R E S U Lt S Attenuation Functionsmentioning
confidence: 77%
“…As discussed in Yenier & Atkinson (2015), a geometrical spreading faster than r −1 at short and intermediate distances is not an uncommon feature, considering that the real propagation medium is far from to be homogenous. A strong geometrical spreading at short and intermediate distances is observed in other worldwide regions, such as Western North America (Atkinson 2004;Babaie Mahani & Atkinson 2012) and Central and Eastern America (Yenier & Atkinson 2015).…”
Section: R E S U Lt S Attenuation Functionsmentioning
confidence: 96%
“…Although a detailed discussion on the source scaling is beyond the aim of this work, we calibrate two parametric models for the stress drop as function of magnitude and depth (e.g. Yeneir & Atkinson 2015a): the first model considers local magnitude whereas the second one adopts the moment magnitude. The best fit models are given by: where γ hl is a depth-dependent adjustment offset equal to −0.1198 for depths h shallower than 8 km, and equal to 0.1198 for h ≥ 8 km when M L is considered; considering M w , the depth-dependent adjustment is γ hw = ±0.14477.…”
Section: Parametric Modelsmentioning
confidence: 99%
“…It is also known that there can be significant regional differences in the value of the median stress parameter. For example, recently Yenier and Atkinson (2015) have found that earthquakes in eastern North America (ENA) attain higher stress parameter values than those in WNA by an average factor of 3. In the context of (median) GMPE adjustment, we investigate the impact of changes in Δσ on response spectrum, y max f osc vis-à-vis the FAS of ground motion.…”
Section: Implications For δσ Adjustmentmentioning
confidence: 99%